Experience in/of Cinema: Gender and Spectatorial Subjectivity in The Great Indian Kitchen - Kavya Krishna K.R.; Kadavath V.K. (My University, 2025)
This chapter reads the Malayalam film The Great Indian Kitchen (Baby, 2021) as a site to disentangle a film text after the OTT revolution and raises questions related to gender, experience, and spectatorial subjectivities. It places “experience” as an important category interlinking problems of cinematic “aesthetics” and the “everyday” that the discourse around the film has generated. Experience is perceived at different levels: the “sensorial experience of the kitchen” which the film created, the numerous personal experiential notes by female audience on social media after watching the film, the altering of the gendered spectatorial subjectivities of the so called “family movie”, and the dalit feminist critique of the female experience provided by the film. We argue that through different formal and aesthetic means, the film creates a “sensorial experience of the kitchen” which unsettles the received perceptions about the kitchen space, especially in relation to reading kitchen as a space of labour. The writings by female audience on social media after watching the film are analysed in detail to understand why they were memoirs or reflections on their own personal life experiences rather than appreciation of the film’s aesthetic and argue that these Facebook notes forge a continuity between the filmic space and the space of the social media as a site for the production of memory/knowledge. It tries to see whether the film’s reception further signals a reconstitution of the familial and spectatorial subjectivities, especially in relation to what the Malayalam film industry has called “the family movie”. The last part of the chapter briefly responds to some of the questions raised from a dalit feminist standpoint in order to problematise the question of experience and its relation to women empowerment today. © 2025 selection and editorial matter, Aysha Viswamohan; individual chapters, the contributors. All rights reserved.